Identification of quantitative trait loci and candidate genes for an anxiolytic‐like response to ethanol in BXD recombinant inbred strains. (April 2016) - Putman, A. H.; Wolen, A. R.; Harenza, J. L.; Yordanova, R. K.; Webb, B. T.; Chesler, E. J.; Miles, M. F.
Abstract : Behavioral genetics and genomic studies were identified as a novel locus modulating anxiolytic‐like activity of ethanol in mice. We validated and fine mapped the most significant ethanol‐anxiolytic QTL on Chr 12, termed Etanq1, and identified a highly promising candidate gene, Ninein . This is a very novel finding and because anxiety is considered a strong co‐morbid factor for the development of alcohol use disorders and recidivism, we believe our studies are highly significant. Abstract : Genetic differences in acute behavioral responses to ethanol contribute to the susceptibility to alcohol use disorder and the reduction of anxiety is a commonly reported motive underlying ethanol consumption among alcoholics. Therefore, we studied the genetic variance in anxiolytic‐like responses to ethanol across the BXD recombinant inbred (RI) mouse panel using the light–dark transition model of anxiety. Strain‐mean genetic mapping and a mixed‐model quantitative trait loci (QTL) analysis replicated several previously published QTL for locomotor activity and identified several novel anxiety‐related loci. Significant loci included a chromosome 11 saline anxiety‐like QTL ( Salanq1 ) and a chromosome 12 locus ( Etanq1 ) influencing the anxiolytic‐like response to ethanol. Etanq1 was successfully validated by studies with BXD advanced intercross strains and fine‐mapped to a region comprising less than 3.5 Mb. Through integration of genome‐wide mRNA expression profiles of the mesocorticolimbic reward circuit (prefrontal cortex, nucleus accumbens and ventral midbrain) across the BXD RI panel, we identified high priority candidate genes within Etanq1, the strongest of which was Ninein ( Nin ), a Gsk3β ‐interacting protein that is highly expressed in the brain.